SAT0530 Development of A Patient Reported Outcome Measure of Tophus Burden: the Tophus Impact Questionnaire (TIQ-20). (10th June 2014) - Aati, O.; Taylor, W.; Seigert, R.; Horne, A.; House, M.; Tan, P.; Drake, J.; Stamp, L.; Dalbeth, N.
Abstract : Background: The tophus represents a chronic foreign body granulomatous response to monosodium urate crystals. Tophi have been associated with activity limitation, joint damage and mortality in people with gout. Currently, tophus burden is measured using physical examination and imaging methods, and no tophus-specific patient reported outcome (PRO) measure exists. Objectives: To develop a PRO tool to assess tophus burden in people with gout. Methods: The responses from interviews with 25 people with tophaceous gout were used to generate items for a preliminary PRO tool. Cognitive testing for each item was performed by interviewing five healthcare professionals and a further five people with tophaceous gout. A preliminary 34-item questionnaire was administered to 103 people with tophaceous gout. Rasch analysis generated a 20-item Tophus Impact Questionnaire (TIQ-20) (maximum score 20). Test-retest reproducibility over a two week interval was assessed in 53 participants, and construct validity was assessed by analysing Spearman's correlations between TIQ-20 scores and other measures of gout severity. Calculated Spearman's correlations were compared with predicted correlations generated by three rheumatologists. Results: The TIQ-20 included items related to pain, activity limitation, footwear modification, participation, psychological impact and healthcare utilisation due to tophi. The TIQ-20 responses fit the Rasch model and demonstrated unidimensionality, adequate precision, absence of differential item functioning, and adequate person separation index. In the 103 patients with tophaceous gout, the median TIQ-20 score was 6 (range 2-19). Floor and ceiling effects were both 0%. The TIQ-20 test-retest intraclass correlation coefficient was 0.72 (95% CI 0.56-0.83). The TIQ-20 scores weakly correlated with serum urate concentrations (r=0.25) and frequency of gout flares (r=0.24), p<0.05 for both. TIQ-20 moderately correlated with HAQ-II scores (r=0.48), subcutaneous tophus count (r=0.42) and dual energy CT urate volume (n=79, r=0.41), p<0.001 for all. With the exception of the HAQ-II, the calculated correlations were consistent with predicted relationships. Conclusions: We have developed and validated a tophus-specific PRO in a population of patients with tophaceous gout. The TIQ-20 demonstrates acceptable psychometric properties. Initial results shows promising face and construct validity, reproducibility and feasibility. Further research is required to determine responsiveness to change. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3364